Effectiveness of Preoperative Red Cell Preparation and Intraoperative Massive Transfusion in Brain Tumor Operation - Tunthanathip, Thara; Sae-heng, Sakchai; Oearsakul, Thakul; Kaewborisutsakul, Anukoon; Taweesomboonyat, Chin (Indian Journal of Neurosurgery, 2023)
Background Excessive requests for preoperative packed red cell (PRC) preparation have been noted, resulting in waste of blood products and higher costs in brain tumor surgery. The objectives of the present study were as follows: (1) the primary objective was to assess the effectiveness index of blood preparation and utilization; (2) the secondary objective was to explore factors associated with intraoperative PRC transfusion; and (3) the third objective was to identify the prevalence and analyze risk factors of massive transfusion.Methods A retrospective cohort study was done on patients who had undergone brain tumor operations. The effectiveness indexes of preoperative PRC preparation and intraoperative utilization were calculated as follows: the crossmatch to transfusion (C/T) ratio, transfusion probability (Tp), and transfusion index (Ti). Additionally, factors associated with intraoperative PRC transfusion and massive transfusion were analyzed.Results There were 1,708 brain tumor patients and overall C/T, Tp, and Ti were 3.27, 45.54%, and 1.10, respectively. Prevalence of intraoperative PRC transfusion was 44.8%, and meningioma, intraosseous/skull-based tumor, and tumor size were linked with massive transfusion.Conclusion Unnecessary preoperative blood component preparation for brain tumor surgery was noticed in routine practice. Exploring intraoperative transfusion variables has been challenged in optimizing crossmatch and actual use.
Keywords: massive transfusion; intraoperative transfusions; brain tumor; blood transfusion